Integrating Advanced Practice Registered Nurses Into Nursing Homes: The Missouri Quality Initiative Experience. Issue 3 (April 2015) - Vogelsmeier, Amy; Popejoy, Lori; Rantz, Marilyn; Flesner, Marcia; Lueckenotte, Annette; Alexander, Greg
Abstract : Supplemental Digital Content is Available in the Text.